Effect of the Lookback Period's Length Used to Identify Incident Acute Myocardial Infarction on the Observed Trends on Incidence Rates and Survival. (July 2015) - Sulo, Gerhard; Igland, Jannicke; Vollset, Stein Emil; Nygård, Ottar; Egeland, Grace M.; Ebbing, Marta; Sulo, Enxhela; Tell, Grethe S.
<x xml:space="preserve">Abstract</x> Background— In studies using patient administrative data, the identification of the first (incident) acute myocardial infarction (AMI) in an individual is based on retrospectively excluding previous hospitalizations for the same condition during a fixed time period (lookback period [LP]). Our aim was to investigate whether the length of the LP used to identify the first AMI had an effect on trends in AMI incidence and subsequent survival in a nationwide study. Methods and Results— All AMI events during 1994 to 2009 were retrieved from the Cardiovascular Disease in Norway project. Incident AMIs during 2004 to 2009 were identified using LPs of 10, 8, 7, 5, and 3 years. For each LP, we calculated time trends in incident AMI and subsequent 28-day and 1-year mortality rates. Results obtained from analyses using the LP of 10 years were compared with those obtained using shorter LPs. In men, AMI incidence rates declined by 4.2% during 2004 to 2009 (incidence rate ratio, 0.958; 95% confidence interval, 0.935–0.982). The use of other LPs produced similar results, not significantly different from the LP of 10 years. In women, AMI incidence rates declined by 7.3% (incidence rate ratio, 0.927; 95% confidence interval, 0.901–0.955) when an LP of 10 years was used. The decline was statistically significantly smaller for the LP of 5 years (6.2% versus 7.3%; P=0.02) and 3 years (5.9% versus 7.3%; P=0.03). The choice of LP did not influence trends in 28-day and 1-year mortality rates. Conclusions— The length of LP may influence the observed time trends in incident AMIs. This effect is more evident in older women.